OP0255-PARE USING AN EDUCATIONAL APPLICATION TO FACILITATE UNDERSTANDING OF THE ANATOMY AND FUNCTION OF THE BRAIN AND TO EXPLORE THE EFFECTS OF CLINICAL FATIGUE FROM A PATIENT PERSPECTIVE. (2nd June 2020) - Zurowski, J.; Wright, C.; Basu, N.; Poyade, M.; Bennett, L.
Abstract : Background: Rheumatic and musculoskeletal diseases are a group of devastating autoimmune disorders that all commonly share the debilitating symptom of fatigue. Despite the fact that fatigue can often cause some of the greatest impairments to quality of life, it is frequently reported by patients as the least successfully managed symptom of these conditions. Fatigue is routinely misunderstood within the general population, with many people using the word fatigue as a synonym for tired. Fatigue is not the same as tiredness, which is a normal state that is experienced by most of the population, therefore it is important to help the general public understand what fatigue actually is and how it imposes consequences and limitations on those who suffer from it. To aid this understanding an educational application has been created to reinforce the patient perspective of living with fatigue. Furthermore, this application will also aid the understanding of brain anatomy and function, using Augmented Reality (AR), as research has now shown that brain function may be altered in the state of fatigue. Currently, educational AR applications show great potential for increasing comprehension and understanding of complex concepts. AR expands user engagement by enhancing the learner's enjoyment and enriching their learning environment. We hope to utilise this technology in the education of fatigue. Objectives: We aimed to create an AR application that has informative content designed to educate users on the topics of basic brain anatomy and function. Furthermore, we aimed to increase the users understanding of the complete impairment of fatigue by creating a short video that describes living with fatigue from the patient's perspective. Methods: The application was created using medical scan dataset, a variety of 3D modelling software, and a game engine to create a functional and interactive augmented application. The short video regarding a patient's perspective on living with fatigue was developed in collaboration with the Glasgow Arthritis Involvement Network patient partners. In order to determine if the application met its primary objectives a pilot test was conducted on 14 participants. After consenting to taking part in the study, individuals were guided through a pre-application test, the use of the application itself and finally a post-application test. Results: Initial results from the pilot test showed promise in the educational potential of the application. With regards to the questions pertaining to the brain anatomy, the percentage of questions answered correctly increased from 36% in the pre-test to 60% in the post-test. Furthermore, after using the application the participants reported a significant increase in their confidence for their answers. An additional six questions ascertained a participants perceptions of fatigue. From these questions, the answer that was most significantly changed after use of the application, was in relation to the impact that fatigue has on a patient's quality of life (t-Test p=0.02). After use of the application participants' opinions changed to reflect the fact that fatigue can completely impair a person's quality of life, showing an increase in their understanding of the debilitating nature of fatigue. Conclusion: This research explored the development and effectiveness of an AR application that was centered around fatigue and basic neuroanatomy education within the general population. From the pilot test conducted we are able to report that the application was successful in delivering educational material about brain anatomy and was successful in increasing awareness about the impact that fatigue can have on an individual's quality of life. Acknowledgments: The Glasgow Arthritis Involvement Network (GAIN) Disclosure of Interests: None declared